SUSTAINABLE DEVELOPMENT STRATEGY: GREEN ECONOMY, ECONOMIC SECURITY, AND HUMAN CAPITAL - Rimma Yunusova, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores the strategic foundations of sustainable development through the integration of green economy principles, economic security mechanisms, and human capital enhancement. The study examines how ecological modernization, structural economic diversification, and workforce development collectively contribute to long-term national resilience. Particular attention is given to institutional coordination, innovation-driven growth, and risk management in conditions of global uncertainty. The research emphasizes that sustainable development requires systemic transformation rather than isolated environmental reforms. The findings demonstrate that balanced interaction between environmental responsibility, economic stability, and intellectual capacity forms the basis for inclusive and competitive development.